FIELD-INDUCED TRANSPORT FOR INTERNAL AND INTERFACE SEGREGATION IN MULTIPHASE POLYMER FLOW SYSTEMS - Khan, M. B. (The Nucleus, 2020)
The primary aim of this paper is to illustrate how certain processing variables influence the polymer structure and the extent of segregation in various flow geometries. A pronounced distinction is made between â€œdiffusionâ€ and â€œfieldinduced segregationâ€. As opposed to diffusion in the classical sense, field-driven transport occurs against the concentration gradient. It is demonstrated that the application of an appropriate lateral field generates transversal migration of suspended material and, in certain cases, the segment domains in the â€œmatrixâ€ polymer. In particular, the potential of shear fields to generate locally segregated flow structures, which might be preserved during the fabrication procedure, has been assessed. Even though one finds a surprisingly large variety of driving forces available for lateral transport, the efficacy of highly specific processes resides in the novel application of boundary conditions. Convectionpromoted shear transport has been investigated as a relevant example with an initial condition which specifies a crossflow velocity component in an existing shear field. The investigation reveals that migratory transport in polymer processing channels has the potential to generate localized changes in the polymer morphology and structure, apart from affecting phase-redistribution of additive species on a more global scale. Experimental evidence on the phasefractionation of poly-dispersed polyethylene and thermosetting polyurethane (PU) clearly demonstrates the phenomenon. The paper describe a new interface segregation system employing convection promoted field-induced transport for use in the thermoset reaction injection molding and other related polymer production processes. The proposed design mitigates the primary limitations of ordinary diffusion and other conventional external field migration system. The basic design concept is described and the key performance parameters are evaluated using established methods. An analytical model describes the time and space evaluation of the transverse concentration profile in the system and the results are compared with the experimental findings.